Assessing Clients in Their Natural Environments With Electronic Diaries: Rationale, Benefits, Limitations, and Barriers. - Piasecki, Thomas M.; Hufford, Michael R.; Solhan, Marika (Psychological Assessment, 2007)
Increasingly, mobile technologies are used to gather diary data in basic research and clinical studies. This article considers issues relevant to the integration of electronic diary (ED) methods in clinical assessment. EDs can be used to gather rich information regarding clients' day-to-day experiences, aiding diagnosis, treatment planning, treatment implementation, and treatment evaluation. The authors review the benefits of using diary methods in addition to retrospective assessments, and they review studies assessing whether EDs yield higher quality data than conventional, less expensive paper-pencil diaries. Practical considerations—including what platforms can be used to implement EDs, what features they should have, and considerations in designing diary protocols for sampling different types of clinical phenomena—are described. The authors briefly illustrate with examples some ways in which ED data could be summarized for clinical use. Finally, the authors consider barriers to clinical adoption of EDs. EDs are likely to become increasingly popular tools in routine clinical assessment as clinicians become more familiar with the logic of diary designs; as software packages evolve to meet the needs of clinicians; and as mobile technologies become ubiquitous, robust, and inexpensive. Reprinted by permission of the publisher.